UV-curable organopolysiloxane composition and its uses
Patent Information
- Application Number
- JP2024574581
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-06-29
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2042-06-29
Smart Images

Figure 0007943924000001
Abstract
Description
[Technical Field]
[0001] The present invention relates to an ultraviolet (UV) curable organopolysiloxane composition containing an organosiloxane and / or organopolysiloxane that can be cured by active light such as ultraviolet light or electron beams, and more particularly to a UV curable organopolysiloxane composition in which the resulting cured product has high hardness and good toughness along with excellent coating ability. The curable organopolysiloxane composition of the present invention has a low viscosity of less than 500 mPas and is suitable as an insulating material for electronic and electrical devices, and especially as a material for use as a coating agent. Furthermore, since this composition is substantially free of organic solvents, it contributes to process simplification. In addition, the cured product obtained by curing the composition has good release properties and is useful as a material for stamps applied to nanoimprint lithography (also referred to as masks, masters, templates, or mold materials). [Background technology]
[0002] Due to their high heat resistance and excellent chemical stability, silicone resins are used as coatings, potting agents, and insulating materials for electronic and electrical devices. UV-curable silicone compositions have also been reported.
[0003] Photolithography is a known process for forming fine patterns in semiconductor devices. Silicone materials for this purpose are also generally known. For example, Japanese Patent Publication No. 2009-298887 discloses a photo-patternable material comprising a polysiloxane obtained by hydrolysis and condensation reactions, a photoacid generator, and an organic solvent.
[0004] On the other hand, nanoimprint lithography has been proposed as an alternative to photolithography processes and is expected to significantly reduce semiconductor manufacturing costs. This technology consists of a process of contacting a stamp with a fine pattern, made from a UV-transparent material such as quartz, with a curable material such as an acrylate resin, a process of curing the curable material, and a process of releasing the stamp from the cured material. The stamp deteriorates with repeated use and needs to be replaced periodically. However, stamps made from quartz are expensive, and stamps made from resin materials are being researched.
[0005] Japanese Patent Publication No. 2015-214637 discloses a nanoimprint master article comprising a laminated body obtained by bonding a cured body from a UV-curable organopolysiloxane resin composition containing a linear organopolysiloxane having at least two alkenyl groups, a three-dimensional resinous organopolysiloxane having a specific amount of alkenyl groups, an organohydrogenpolysiloxane having at least two silicon-bonded hydrogen atoms in the molecule and not containing alkoxy groups, and a photoactivated hydrosilylation catalyst, to a thermoplastic resin substrate. However, because this composition has a high content of linear organopolysiloxane having at least two alkenyl groups, it forms an elastomeric cured body with low hardness. Furthermore, the viscosity of the composition is higher than 2700 mPas, making it unsuitable for coating process applications such as spin coating.
[0006] Furthermore, Japanese Patent Publication No. 2010-47646 describes branched organopolysiloxanes having at least three alkenyl groups, linear organopolysiloxanes having at least two alkenyl groups, and SiO 4 / 2 Units and R 3 SiO 1 / 2A UV-curable organopolysiloxane resin composition is disclosed, comprising an organohydrogenpolysiloxane having at least three silicon-bonded hydrogen atoms in its molecule, and a (methylcyclopentadienyl)trialkylplatinum complex. Although the cured product from this composition has sufficiently high hardness due to its high content of branched organopolysiloxane, the composition is not suitable for coating process applications such as spin coating due to its high viscosity of 5,100 mPas.
[0007] On the other hand, Japanese Patent Publication No. 2005-227701 discloses a curable organopolysiloxane resin composition applicable to optical transmission articles, comprising an organopolysiloxane having at least two silicon-bonded alkenyl groups in its molecule, an organopolysiloxane or organosilicon compound having at least two silicon-bonded hydrogen atoms in its molecule, and a hydrosilylation reaction catalyst. This composition has a low viscosity of 800 mPas or less, and its cured product has good flexibility. However, the relationship between the mechanical strength and molecular weight of the cured product of the branched organopolysiloxane has not been studied at all. In addition, the cured product from this composition does not have sufficiently high hardness. Furthermore, this patent document makes no mention of UV curability. [Prior art documents] [Patent Documents]
[0008] Patent Document 1: Japanese Unexamined Patent Publication No. 2015-214637 Patent Document 2: Japanese Unexamined Patent Publication No. 2010-047646 Patent Document 3: Japanese Unexamined Patent Publication No. 2005-227701 [Overview of the project]
[0009] Problems that the invention aims to solve As described above, low-viscosity organopolysiloxane compositions applied to curable organopolysiloxane compositions and nanoimprint stamp articles are known, but there is still a need for UV-curable organopolysiloxane compositions whose cured products have sufficient hardness and toughness, excellent workability for application to substrates, and particularly low viscosity. That is, the object of the present invention is to provide a UV-curable organopolysiloxane composition in which the cured product obtained by curing has sufficient hardness and toughness, along with particularly excellent workability, when applied to a substrate.
[0010] Means for solving the problem The present invention is completed by designing the composition of a UV-curable organopolysiloxane composition in which the viscosity of the entire composition, measured at 25°C using an E-type viscometer, is in the range of more than 80 mPas and less than or equal to 500 mPas, without containing any organic solvents in the composition, and by controlling the content of alkenyl groups in the composition, the curable composition has excellent workability, such as coating ability, and the hardness and toughness of the cured product therefrom is sufficiently high. This is achieved by using (A) a mixture of at least two types of branched organopolysiloxanes having at least two alkenyl groups in the molecule and having different molecular weights, and linear organopolysiloxanes having at least two alkenyl groups in the molecule, and (B) an organopolysiloxane having two or more silicon-bonded hydrogen atoms in the molecule, and a photoactivated hydrosilylation catalyst.
[0011] The ultraviolet (UV) curable organopolysiloxane composition of the present invention is (A1) A branched organopolysiloxane having two or more alkenyl groups in the molecule and a molecular weight of 2,500 or more, (A2) A branched organopolysiloxane having two or more alkenyl groups in the molecule and a molecular weight of less than 2,500, (A3) A linear organopolysiloxane having two or more alkenyl groups in the molecule, (B) an organopolysiloxane, which has two or more silicon-bonded hydrogen atoms in the molecule, in an amount within a range where the molar ratio of the silicon-bonded hydrogen atoms in component (B) to the alkenyl groups in component (A) is 0.5 to 4.0; and (C) a photoactivated hydrosilylation catalyst,[ wherein the mass ratio of components (A1), (A2), and (A3) satisfies the following formula (1): [(A1)+(A2)] / (A3)>1.3 (1) the alkenyl group content X per 100 g of the entire composition satisfies the following formula (2): 110≦X≦220 (2), the viscosity of the entire composition measured at 25°C using an E-type viscometer is in a range of more than 80 mPas to 500 mPas or less, and an organic solvent is not substantially contained in the composition.
[0012] When the total mass of components (A) to (C) in the composition is 100 parts by mass, the parts by mass of components (A1), (A2), and (A3) preferably satisfy the following: (A1): 25 to 75 parts by mass, (A2): 3 to 60 parts by mass, and (A3): 5 to 40 parts by mass.
[0013] Component (A3) is preferably a linear organopolysiloxane having an alkenyl group at its molecular terminal.
[0014] Component (B) is preferably a linear organopolysiloxane having two or more silicon-bonded hydrogen atoms in the molecule.
[0015] Component (A1) has an alkenyl group, and is represented by the following average unit formula: (R 1 3SiO 1 / 2 ) a1 (R 1 2SiO 2 / 2 ) b1 (R 1 SiO 3 / 2 ) c1 (SiO 4 / 2 ) d1 (3) (wherein, R 1 are each independently a monovalent hydrocarbon group having 1 to 12 carbon atoms, at least 2 of all R 1 are alkenyl groups having 2 to 12 carbon atoms, and a1, b1, c1, and d1 are numbers satisfying the following conditions: a1+b1+c1+d1=1, 0≦a1≦0.5, 0≦b1≦0.4, 0≦c1≦0.8, 0≦d1≦0.7, and 0.5≦c1+d1≦0.8), it is preferably a branched organopolysiloxane.
[0016] Component (A2) has an alkenyl group, and is represented by the following average unit formula: (R 2 3SiO 1 / 2 ) a2 (R 2 2SiO 2 / 2 ) b2 (R 2 SiO 3 / 2 ) c2 (SiO 4 / 2 ) d2 (4) (wherein, R 2 are each independently a monovalent hydrocarbon group having 1 to 12 carbon atoms, at least 2 of all R 2 are alkenyl groups having 2 to 12 carbon atoms, and a2, b2, c2, and d2 are numbers satisfying the following conditions: a2+b2+c2+d2=1, 0≦a2≦0.5, 0≦b2≦0.8, 0≦c2<0.5, 0≦d2<0.5, and 0<c2+d2<0.5), it is preferably a branched organopolysiloxane.
[0017] It is preferable that the mass ratio of components (A1), (A2), and (A3) satisfies the following formula: [(A1)+(A2)] / (A3)≧1.5 (5).
[0018] For the cured product obtained by curing the composition, the hardness measured at 25°C using a Type D durometer is preferably 30 or more.
[0019] The viscosity of the entire composition, as measured at 25°C using an E-type viscometer, is preferably in the range of 100 to 350 mPas.
[0020] Component (C) is preferably an unsubstituted or alkyl-substituted (cyclopentadienyl) trialkyl platinum complex.
[0021] The UV-curable organopolysiloxane composition of the present invention is suitable for use as an insulating coating agent. Accordingly, the present invention provides an insulating coating agent comprising the UV-curable organopolysiloxane composition.
[0022] Furthermore, the present invention provides a cured product obtained by curing the UV-curable organopolysiloxane composition.
[0023] Furthermore, the present invention provides the use of the UV-curable organopolysiloxane composition as a stamp-forming material applied to nanoimprint lithography.
[0024] Effects of the invention The UV-curable organopolysiloxane composition of the present invention has low viscosity without the use of organic solvents, exhibits excellent coating ability to substrates via processes such as spin coating, has good curability, and the cured product obtained by curing has sufficiently high hardness and good toughness. [Modes for carrying out the invention]
[0025] First, the UV-curable organopolysiloxane composition of the present invention (hereinafter, it may be referred to as the "curable composition" or "UV-curable composition") will be described in more detail below. Furthermore, in the present invention, molecular weight refers to the weight-average molecular weight relative to standard polystyrene, measured by gel permeation chromatography (GPC).
[0026] The curable composition of the present invention, (A1) A branched organopolysiloxane having two or more alkenyl groups in the molecule and a molecular weight of 2,500 or more, (A2) A branched organopolysiloxane having two or more alkenyl groups in the molecule and a molecular weight of less than 2,500, (A3) A linear organopolysiloxane having two or more alkenyl groups in the molecule, (B) An organopolysiloxane having two or more silicon-bonded hydrogen atoms in the molecule in an amount such that the molar ratio of silicon-bonded hydrogen atoms in component (B) to alkenyl groups in component (A) is in the range of 0.5 to 4.0, (C) photoactivation hydrosilylation catalyst, comprising The mass ratios of components (A1), (A2), and (A3) satisfy the following equation (1): [(A1)+(A2)] / (A3)>1.3 (1) The amount of alkenyl groups X per 100g of the entire composition satisfies the following equation (2): 110 ≤ X ≤ 220 (2), The viscosity of the entire composition, measured at 25°C using an E-type viscometer, is in the range of over 80 mPas and up to 500 mPas. The composition is characterized by being substantially free of organic solvents.
[0027] When this UV-curable composition contains component (C) of a photoactivated hydrosilylation catalyst, irradiation with active light, such as UV rays, activates the catalyst in the form of a hydrosilylation reaction catalyst, and it hardens by crosslinking caused by the addition reaction between the alkenyl group in component (A) and the silicon-bonded hydrogen atom (Si-H), i.e., the hydrosilyl group, in component (B).
[0028] Components (A), (B), (C), and other optional components are described in further detail below.
[0029] [Ingredients (A)] Component (A) is the main component of this composition and is a mixture of organopolysiloxanes having alkenyl groups. Specifically, component (A) consists of the following components (A1), (A2), and (A3), and the mass ratio of each component satisfies a specific relationship.
[0030] [Component (A1): A branched organopolysiloxane having two or more alkenyl groups in the molecule and a molecular weight of 2,500 or more] Component (A1) is an organopolysiloxane having a curable group containing an alkenyl group, i.e., a carbon-carbon double bond. The carbon-carbon double bond may react with a Si-H group by a hydrosilylation reaction and is not limited to alkenyl groups having a specific chemical structure. Preferably, the alkenyl group is an alkenyl group at the molecular terminal, and examples include, but are not limited to, C2-C20 alkenyl groups such as vinyl group, allyl group, butenyl group, pentenyl group, hexenyl group, heptenyl group, octenyl group, nonenyl group, decenyl group, undecenyl group, dodecenyl group, and 4-vinylphenyl group. The alkenyl group is particularly preferably selected from vinyl group, allyl group, and hexenyl group, with vinyl group being the most preferred.
[0031] The branched organopolysiloxane of component (A1) is branched, more specifically having a branched chain structure or a resinous (network) structure, containing two or more of the alkenyl groups in its molecule, and having a molecular weight of 2,500 or more, preferably 3,000 or more. By incorporating this high molecular weight branched organopolysiloxane, the hardness and toughness of the cured product obtained by curing the composition are improved. Component (A1) preferably contains 25 or more, more preferably 30 or more silicon atoms. One type or a combination of at least two types of branched organopolysiloxanes can be used as component (A1).
[0032] In addition to the alkenyl group, the branched organopolysiloxane of component (A1) may contain any functional group selected from the group consisting of monovalent hydrocarbon groups, hydroxyl groups, and alkoxy groups that do not contain carbon-carbon double bonds in the molecule. Examples of monovalent hydrocarbon groups include unsubstituted monovalent hydrocarbon groups and fluorine-substituted monovalent hydrocarbon groups. Unsubstituted or fluorine-substituted monovalent hydrocarbon groups are preferably groups selected from unsubstituted or fluorine-substituted alkyl groups, cycloalkyl groups, arylalkyl groups, and aryl groups having 1 to 20 carbon atoms. Examples of alkyl groups include methyl group, ethyl group, n-propyl group, isopropyl group, n-butyl group, tert-butyl group, sec-butyl group, pentyl group, octyl group, and other groups, with methyl group being particularly preferred. Examples of cycloalkyl groups include cyclopentyl group and cyclohexyl group. Examples of arylalkyl groups include benzyl group and phenylethyl group. Examples of aryl groups include phenyl group and naphthyl group. Examples of fluorine-substituted monovalent hydrocarbon groups include the 3,3,3-trifluoropropyl group and the 3,3,4,4,5,5,5,6,6,6-nonafluorohexyl group. The 3,3,3-trifluoropropyl group is preferred as the fluorine-substituted monovalent hydrocarbon group.
[0033] In the branched organopolysiloxane of component (A1), the Si-bonded organic groups other than the alkenyl groups are preferably essentially methyl groups. That is, of all Si-bonded organic groups other than the alkenyl groups, preferably 95 mol% or more, more preferably 99 mol% or more, and most preferably 100 mol% are methyl groups. Therefore, the most preferred embodiment of component (A1) is an organosiloxane having a vinyl group as the alkenyl group and the Si-bonded organic groups other than the alkenyl groups being essentially methyl groups, and is preferably one type or a combination of at least two types selected from the group of branched organopolysiloxanes and resinous organopolysiloxanes (irganopolysiloxanes).
[0034] The branched organopolysiloxane component (A1) is usually in a solid state, but its state can vary depending on its molecular weight, molecular weight distribution, and the type of substituents on the Si atoms. When preparing the UV-curable organopolysiloxane composition of the present invention, component (A1) can be directly incorporated as one of the raw materials. On the other hand, in order to simplify the manufacturing process, it is preferable to incorporate component (A1) as a liquid mixture by pre-mixing it with another organopolysiloxane, specifically a linear organopolysiloxane (A3) having an alkenyl group.
[0035] Preferably, component (A1) is a branched organopolysiloxane or a mixture of two or more types represented by the following average unit formula: (R 1 3SiO 1 / 2 ) a1 (R 1 2SiO 2 / 2 ) b1 (R 1 SiO 3 / 2 ) c1 (SiO 4 / 2 ) d1 (3) In the formula, R 1 It is a monovalent hydrocarbon group having 1 to 12 carbon atoms independently, and all R 1 At least two of these are alkenyl groups having 2 to 12 carbon atoms, and a1, b1, c1, and d1 are numbers that satisfy the following conditions: a1 + b1 + c1 + d1 = 1, 0 ≤ a1 ≤ 0.5, 0 ≤ b1 ≤ 0.4, 0 ≤ c1 ≤ 0.8, 0 ≤ d1 ≤ 0.7, and 0.5 ≤ c1 + d1 ≤ 0.8. 1The aforementioned groups can be used when a1, b1, c1, and d1 represent an alkenyl group and another monovalent hydrocarbon group having 1 to 12 carbon atoms. With respect to the preferred proportion of each siloxane unit, if a1, b1, c1, and d1 are within the specified range, a high molecular weight of the branched organopolysiloxane can be easily designed. Furthermore, if c1+d1 is greater than the lower limit, it is preferable because the molecular weight of the branched organopolysiloxane tends to be higher. On the other hand, if c1+d1 is lower than the upper limit, it is preferable because it enables more stable production of the branched organopolysiloxane.
[0036] Examples of branched organopolysiloxanes having alkenyl groups that can be used as component (A1) include organopolysiloxanes represented by the following average unit formula. In the following formula, Me, Vi, and Ph represent methyl, vinyl, and phenyl groups, respectively, and n, m, l, and k represent the molar ratio of each siloxane unit, each greater than 0 and less than 1, provided that these values satisfy the condition n+m+l+k=1. (Me3SiO 1 / 2 ) n (Me2ViSiO 1 / 2 ) m (SiO 4 / 2 ) l [0.5≦l] (Me2ViSiO 1 / 2 ) n (SiO 4 / 2 ) m [0.5≦m] (Me3SiO 1 / 2 ) n (Me2ViSiO 1 / 2 ) m (Me2SiO 2 / 2 ) l (SiO 4 / 2 ) k [0.5≦k] (Me2ViSiO 1 / 2 ) n (Me2SiO 2 / 2 ) m (SiO 4 / 2 ) l [0.5≦l] (Me3SiO1 / 2 ) n (MeViSiO) 2 / 2 ) m (SiO 4 / 2 ) l [0.5≦l] (Me2ViSiO 1 / 2 ) n (MeSiO 3 / 2 ) m [0.5≦m] (Me3SiO 1 / 2 ) n (Me2ViSiO 1 / 2 ) m (MeSiO 3 / 2 ) l [0.5≦l] (Me3SiO 1 / 2 ) n (Me2ViSiO 1 / 2 ) m (Me2SiO 2 / 2 ) l (MeSiO 3 / 2 ) k [0.5≦k] (Me2ViSiO 1 / 2 ) n (Me2SiO 2 / 2 ) m (MeSiO 3 / 2 ) l [0.5≦l] (Me2ViSiO 1 / 2 ) n (PhSiO 3 / 2 ) m [0.5≦m] (Me2ViSiO 1 / 2 ) n (Me2SiO 2 / 2 ) m (PhSiO 3 / 2 ) l [0.5≦l] (Me2ViSiO 1 / 2 ) n (MePhSiO 2 / 2 ) m (PhSiO 3 / 2 ) l [0.5≦l] (Me2ViSiO 1 / 2 ) n (Ph2SiO 2 / 2 )m (PhSiO 3 / 2 ) l [0.5≦l]
[0037] The organopolysiloxane of component (A1) may contain small amounts of silanol or alkoxysilyl groups that do not affect its hydrosilylation reaction. In this specification, "small amounts" means less than 5 mol% of all substituents bonded to the Si atom.
[0038] [Component (A2): A branched organopolysiloxane having two or more alkenyl groups in the molecule and a molecular weight of less than 2,500] The organopolysiloxane of component (A2), like component (A1), is an organopolysiloxane having a curable group containing an alkenyl group, i.e., a carbon-carbon double bond. The carbon-carbon double bond may react with a Si-H group by a hydrosilylation reaction and is not limited to an alkenyl group having a specific chemical structure. The alkenyl group is particularly preferably selected from vinyl, allyl, and hexenyl groups, with vinyl being the most preferred.
[0039] The branched organopolysiloxane of component (A2) is branched, more specifically having a branched chain structure or a resinous (network) structure, having two or more of the alkenyl groups in the molecule, and having a molecular weight of less than 2,500, preferably less than 2,000, and is usually liquid. By incorporating this liquid branched organopolysiloxane with a lower molecular weight, the viscosity of the entire composition is reduced and its coating ability is improved. Furthermore, by using component (A2) in combination, it contributes to increasing the hardness of the cured product obtained by curing the composition. Component (A2) preferably contains less than 25 silicon atoms, more preferably less than 20. As component (A2), one type or a combination of at least two types of branched organopolysiloxanes can be used.
[0040] In addition to the alkenyl group, the branched organopolysiloxane of component (A2) may contain any functional group selected from the group consisting of monovalent hydrocarbon groups, hydroxyl groups, and alkoxy groups that do not contain a carbon-carbon double bond in the molecule. In this specification, the same groups exemplified in component (A1) can be used as these functional groups.
[0041] In the branched organopolysiloxane of component (A2), the Si-bonded organic groups other than the alkenyl groups are preferably essentially methyl groups. That is, of all Si-bonded organic groups other than the alkenyl groups, preferably 95 mol% or more, more preferably 99 mol% or more, and most preferably 100 mol% are methyl groups. Therefore, the most preferred embodiment of component (A2) is an organosiloxane having a vinyl group as the alkenyl group and the Si-bonded organic groups other than the alkenyl groups being essentially methyl groups, and is preferably one type or a combination of at least two types selected from the group of branched-chain organopolysiloxanes and resinous organopolysiloxanes (irganopolysiloxanes).
[0042] Preferably, component (A2) is a branched organopolysiloxane or a mixture of two or more types represented by the following average unit formula: (R 2 3SiO 1 / 2 ) a2 (R 2 2SiO 2 / 2 ) b2 (R 2 SiO 3 / 2 ) c2 (SiO 4 / 2 ) d2 (4) In the formula, R 2 It is a monovalent hydrocarbon group having 1 to 12 carbon atoms independently, and all R 2at least 2 of them are alkenyl groups having 2 to 12 carbon atoms, and a2, b2, c2, and d2 are numbers satisfying the following conditions: a2+b2+c2+d2=1, 0≦a2≦0.5, 0≦b2≦0.8, 0≦c2<0.5, 0≦d2<0.5, and 0<c2+d2<0.5. R 2 represents an alkenyl group and another monovalent hydrocarbon group having 1 to 12 carbon atoms, the group R 1 can use the aforementioned groups. With respect to the preferred proportion of each siloxane unit, when a2, b2, c2, and d2 are within the aforementioned ranges, a lower molecular weight of the branched organopolysiloxane can be easily designed. Furthermore, when c2+d2 is within the aforementioned range, it is preferable to form a branched organopolysiloxane, which tends not to have an excessively high molecular weight.
[0043] Examples of the alkenyl group-containing branched organopolysiloxane that can be used as the component (A2) include organopolysiloxanes represented by the following average unit formula. In the following formulae, Me, Vi, and Ph each represent a methyl group, a vinyl group, and a phenyl group, respectively, n, m, l, and k each represent the molar ratio of each siloxane unit, each of which is more than 0 and less than 1, provided that these values satisfy the condition of n+m+l+k=1. (Me3SiO 1 / 2 ) n (Me2ViSiO 1 / 2 ) m (SiO 4 / 2 ) l [l<0.5] (Me2ViSiO 1 / 2 ) n (SiO 4 / 2 ) m [m<0.5, preferably, an organopolysiloxane satisfying 3.0≦n / m≦4.0 (Me3SiO 1 / 2 ) n (Me2ViSiO 1 / 2 ) m (Me2SiO 2 / 2 ) l (SiO 4 / 2 ) k [k<0.5] (Me2ViSiO 1 / 2 ) n (Me2SiO 2 / 2 ) m (SiO 4 / 2 ) l [l<0.5] (Me3SiO 1 / 2 ) n (MeViSiO 2 / 2 ) m (SiO 4 / 2 ) l [l<0.5] (Me2ViSiO 1 / 2 ) n (MeSiO 3 / 2 ) m [Organopolysiloxane satisfying m < 0.5, preferably 1.5 ≤ n / m ≤ 3.0] (Me3SiO 1 / 2 ) n (Me2ViSiO 1 / 2 ) m (MeSiO 3 / 2 ) l [l<0.5] (Me3SiO 1 / 2 ) n (Me2ViSiO 1 / 2 ) m (Me2SiO 2 / 2 ) l (MeSiO 3 / 2 ) k [k<0.5] (Me2ViSiO 1 / 2 ) n (Me2SiO 2 / 2 ) m (MeSiO 3 / 2 ) l [l<0.5] (Me2ViSiO 1 / 2 ) n (PhSiO 3 / 2 ) m [Organopolysiloxane satisfying m < 0.5, preferably 1.5 ≤ n / m ≤ 3.0] (Me2ViSiO 1 / 2 ) n (Me2SiO 2 / 2 ) m (PhSiO 3 / 2 ) l[l<0.5] (Me2ViSiO 1 / 2 ) n (MePhSiO 2 / 2 ) m (PhSiO 3 / 2 ) l [l<0.5] (Me2ViSiO 1 / 2 ) n (Ph2SiO 2 / 2 ) m (PhSiO 3 / 2 ) l [l<0.5]
[0044] The organopolysiloxane of component (A2) may contain small amounts of silanol or alkoxysilyl groups that do not affect its hydrosilylation reaction. In this specification, "small amounts" means less than 5 mol% of all substituents bonded to the Si atom.
[0045] [Component (A3): Linear organopolysiloxane having two or more alkenyl groups in the molecule] Component (A3), like components (A1) and (A2), is a linear organopolysiloxane having an alkenyl group, i.e., a curable group containing a carbon-carbon double bond. The carbon-carbon double bond may react with a Si-H group by a hydrosilylation reaction and is not limited to an alkenyl group having a specific chemical structure. The alkenyl group is particularly preferably selected from vinyl, allyl, and hexenyl groups, with vinyl being the most preferred.
[0046] Component (A3) is a linear organopolysiloxane having an average of two or more alkenyl groups in its molecule. From the viewpoint of providing flexibility and toughness to the cured product from the curable composition, component (A3) is preferably a linear organopolysiloxane having alkenyl groups at both ends. The degree of polymerization of component (A3), i.e., the number of silicon atoms it contains, is not limited, but component (A3) can contain an average of five or more silicon atoms per molecule, more preferably ten or more, and further, an average of 1000 or fewer silicon atoms per molecule, more preferably 500 or fewer. In particular, from the viewpoint of controlling the viscosity of the curable composition, component (A3) preferably contains 30 to 200 silicon atoms. By incorporating this component (A3), the viscosity of the entire composition is reduced in the cured product obtained by curing the composition, and its flexibility and toughness are improved. One type or a combination of at least two types of linear organopolysiloxane having alkenyl groups can be used.
[0047] In addition to the alkenyl group, the linear organopolysiloxane of component (A3) may contain any functional group selected from the group consisting of monovalent hydrocarbon groups, hydroxyl groups, and alkoxy groups that do not contain a carbon-carbon double bond in the molecule. In this specification, the same groups exemplified in components (A1) and (A2) can be used as these functional groups.
[0048] In the linear organopolysiloxane of component (A3), similar to component (A1) or component (A2), the Si atom-bonded organic groups other than the alkenyl groups are preferably essentially methyl groups. That is, of all silicon atom-bonded organic groups other than the alkenyl groups, preferably 95 mol% or more, more preferably 99 mol% or more, and most preferably 100 mol% are methyl groups. Therefore, the most preferred embodiment of component (A3) is a linear organosiloxane having a vinyl group as the alkenyl group and the silicon atom-bonded organic groups other than the alkenyl groups being essentially methyl groups, preferably one type or a combination of at least two types of linear organopolysiloxanes having vinyl groups at both ends.
[0049] Examples of linear organopolysiloxanes having alkenyl groups that can be used as component (A3) include organopolysiloxanes represented by the following average unit formula. In the following formula, Me, Vi, and Ph represent methyl, vinyl, and phenyl groups, respectively, and n, m, and l represent the molar ratios of each siloxane unit, each greater than 0 and less than 1, provided that these values satisfy the condition n+m+l=1. (Me2ViSiO 1 / 2 ) n (Me2SiO 2 / 2 ) m (Me2ViSiO 1 / 2 ) n (Me2SiO 2 / 2 ) m (MeViSiO 2 / 2 ) l (Me3SiO 1 / 2 ) n (Me2SiO 2 / 2 ) m (MeViSiO 2 / 2 ) l (Me3SiO 1 / 2 ) n (MeViSiO 2 / 2 ) m (Me2ViSiO 1 / 2 )n (MePhSiO 2 / 2 ) m (Me2ViSiO 1 / 2 ) n (Me2SiO 2 / 2 ) m (Ph2SiO 2 / 2 ) l (Me2ViSiO 1 / 2 ) n (Ph2SiO 2 / 2 ) m (Me3SiO 1 / 2 ) n (MePhSiO 2 / 2 ) m (MeViSiO 2 / 2 ) l (Me3SiO 1 / 2 ) n (Ph2SiO 2 / 2 ) m (MeViSiO 2 / 2 ) l
[0050] When the total mass of components (A) to (C) in the composition is 100 parts by mass, the parts by mass of components (A1), (A2), and (A3) are preferably as follows: (A1): 25 to 75 parts by mass, (A2): 3 to 60 parts by mass, and (A3): 5 to 40 parts by mass. The mass ratios of components (A1), (A2), and (A3) can be determined by considering the viscosity of the composition and the hardness and toughness of the cured product obtained by curing the composition.
[0051] In the curable composition of the present invention, the mass ratio of components (A1), (A2), and (A3) must satisfy the following formula (1): [(A1)+(A2)] / (A3)>1.3 (1) This equation (1) means that the mass ratio of branched organopolysiloxanes (A1, A2) to linear organopolysiloxanes is greater than 1.3. From the viewpoint of hardness, and especially the hardness of a cured product suitable as a stamp material applied to nanoimprint lithography, a preferred value for this mass ratio is 1.5 or higher. A value in the range of 1.5 to 10.0 is more preferred. On the other hand, if the value is 1.3 or less, the proportion of linear organopolysiloxanes in the composition is higher, resulting in lower hardness of the cured product, and the objective of the present invention cannot be achieved.
[0052] Furthermore, the alkenyl group content (X, in millimoles) per 100g of the entire organopolysiloxane composition must satisfy the following formula (2): 110 ≤ X ≤ 220 (2) If this value is lower than 110, it becomes difficult to design a composition with a viscosity suitable for application in the coating process, or the cured product tends to have lower hardness. On the other hand, if the value exceeds 220, the toughness of the cured product becomes worse, and the objectives of the present invention cannot be achieved. The range of the X value is preferably 130 ≤ X ≤ 200, and more preferably 130 ≤ X ≤ 180.
[0053] [Component (B): Organopolysiloxane containing two or more silicon-bonded hydrogen atoms in the molecule] The organopolysiloxane having silicon-bonded hydrogen atoms of component (B) (hereinafter, it may be referred to as "organohydrogenpolysiloxane") has an average of two or more silicon-bonded hydrogen atoms in its molecule and can act as a crosslinking agent to form a crosslinked structure through its hydrosilylation reaction with component (A) having an alkenyl group.
[0054] One or more types selected from the group consisting of organohydrogenpolysiloxanes having linear, branched, cyclic, and resinous forms can be used as component (B). Such organohydrogenpolysiloxanes are well-known compounds in the art of the present invention.
[0055] In the case of component (B), linear organohydrogenpolysiloxanes are exemplified as, but are not limited to, 1,1,3,3-tetramethyldisiloxane, methylhydrogenpolysiloxane with both ends of the molecular chain sealed with trimethylsiloxy groups, dimethylsiloxane / methylhydrogensiloxane copolymer with both ends of the molecular chain sealed with trimethylsiloxy groups, dimethylpolysiloxane with both ends of the molecular chain sealed with dimethylhydrogensiloxy groups, dimethylsiloxane / methylhydrogensiloxane copolymer with both ends of the molecular chain sealed with dimethylhydrogensiloxy groups, methylhydrogensiloxane / diphenylsiloxane copolymer with both ends of the molecular chain sealed with trimethylsiloxy groups, and methylhydrogensiloxane / diphenylsiloxane / dimethylsiloxane copolymer with both ends of the molecular chain sealed with trimethylsiloxy groups. One type or a combination of at least two types of these linear organohydrogenpolysiloxanes can be used. Component (B) of the present invention is such that, of the silicon-bonded organic groups in the organohydrogenpolysiloxane other than silicon-bonded hydrogen atoms, preferably 80 mol% or more, more preferably 90-100 mol%, of said organic groups are methyl groups.
[0056] Examples of component (B) include branched, cyclic, and resinous organohydrogenpolysiloxanes, such as hydrolysis condensation products of 1,3,5,7-tetramethylcyclotetrasiloxane, tris(dimethylhydrogensiloxy)methylsilane, tris(dimethylhydrogensiloxy)phenylsilane, tetrakis(dimethylhydrogensiloxy)silane, trimethoxysilane, and mixtures of two or more types selected therefrom. Further examples of resinous organohydrogenpolysiloxanes include M H MQ type, M H Q type, M H MT type, M H T-type, M H M H QT type, M HMDQ type, M H MDD H Q type, M H DQ type, M H DD H Q type, M H MDT type, M H MDD H T-type, M H DT type, M H DD H T-type, M H MDQT type, M H MDD H QT type, M H DQT type, and M H DD H The at least one organohydrogen polysiloxane resin selected from the QT type, wherein the organohydrogen polysiloxane is SiO 4 / 2 Units (Q units) and R 3 SiO 3 / 2 Unit (T unit), R 3 3SiO 1 / 2 Units (M units), R 3 3HSiO 1 / 2 Unit (M) H It contains at least one branched siloxane unit selected from the units, and optionally, R 3 2SiO 2 / 2 Units (D units), R 3 HSiO 2 / 2 Unit (D H Contains (units). One type or a combination of two or more types can be used. Furthermore, the R 3 This group can independently be a methyl group or a phenyl group, and is preferably a methyl group.
[0057] The branched, cyclic, or resinous organohydrogenpolysiloxane of component (B) may contain small amounts of silanol groups or alkoxysilyl groups that do not affect its hydrosilylation reaction. In this specification, "small amounts" means less than 5 mol% of all substituents bonded to the Si atom.
[0058] As component (B), one or more types of linear, branched, cyclic, and resinous organohydrogenpolysiloxanes can be used. Linear organohydrogenpolysiloxanes are preferred.
[0059] The hydrogen content of the silicon atom-bonded hydrogen radicals of the organohydrogenpolysiloxane in component (B) of the present invention is preferably within 0.1 to 1.6% by mass, more preferably within 0.2 to 1.5% by mass, and most preferably within 0.4 to 1.5% by mass.
[0060] The viscosity of component (B) at 25°C is preferably 2 to 100 mPas, but when combined with components (A) and (C), an organohydrogenpolysiloxane can be used that has an arbitrarily selectable viscosity in the range of over 80 mPas to 500 mPas when measured at 25°C using an E-type viscometer for the entire composition.
[0061] In the curable composition of the present invention, the content of component (A) is such that the amount of silicon-bonded hydrogen atoms in component (B) is in the range of 0.5 to 4.0 moles, preferably 0.7 to 3.0 moles, and most preferably 0.7 to 2.0 moles, per mole of alkenyl groups in component (A). When the amount of silicon-bonded hydrogen atoms in component (B) is within this range, a curable composition can be obtained in which the cured product has good curability and excellent physical properties.
[0062] [Component (C): Photoactivated hydrosilylation catalyst] Component (C) is a photoactivated hydrosilylation catalyst that provides curability to the curable composition of the present invention by irradiation with active light (e.g., UV light). UV (ultraviolet) irradiation with a wavelength of 280-380 nm is industrially feasible for activating component (C). The exposure amount depends on the type of high-energy ray-activated catalyst. In the case of ultraviolet light, the total exposure at a wavelength of 365 nm is preferably 100 mJ / cm². 2 ~10J / cm 2 It is within the range.
[0063] Component (C) is not limited to a specific compound as long as it is a compound that exhibits catalytic activity as a hydrosilylation catalyst upon UV irradiation, but it is preferable to use a photoactivated platinum complex. Examples of such photoactivated platinum complexes include (methylcyclopentadienyl)trimethylplatinum(IV), (cyclopentadienyl)trimethylplatinum(IV), (1,2,3,4,5-pentamethylcyclopentadienyl)trimethylplatinum(IV), (cyclopentadienyl)dimethylethylplatinum(IV), (cyclopentadienyl)dimethylacetylplatinum(IV), (trimethylsilylcyclopentadienyl)trimethylplatinum(IV), (methoxycarbonylcyclopentadienyl)trimethylplatinum(IV), (dimethylphenylsilylcyclopentadienyltrimethylcyclopentadienylplatinum( Examples include IV), trimethyl(acetylacetonato)platinum(IV), trimethyl(3,5-heptanedionato)platinum(IV), trimethyl(methylacetoacetate)platinum(IV), bis(2,4-pentanedionato)platinum(II), bis(2,4-hexanedionato)platinum(II), bis(2,4-heptanedionato)platinum(II), bis(3,5-heptanedionato)platinum(II), bis(1-phenyl-1,3-butanedionato)platinum(II), bis(1,3-diphenyl-1,3-propanedionato)platinum(II), and bis(hexafluoroacetylacetonato)platinum(II).
[0064] As component (C), (cyclopentadienyl)trialkylplatinum complexes or derivatives thereof obtained by substituting the cyclopentadienyl ligand with an alkyl group are preferred, and (methylcyclopentadienyl)trimethylplatinum(IV) is preferred from the standpoint of versatility and availability. Also, as component (C), bis(2,4-pentanedionato)platinum(II) is preferred from the standpoint of versatility and availability.
[0065] The amount of component (C) is the amount necessary to cure the curable composition of the present invention at an industrially sufficient curing rate. The amount of platinum metal atoms in component (C) is in the range of 1 to 500 ppm, preferably in the range of 5 to 100 ppm, and more preferably in the range of 10 to 100 ppm, relative to the mass of the UV-curable organopolysiloxane composition.
[0066] The curable composition of the present invention may optionally contain a hydrosilylation inhibitor. Typically, hydrosilylation inhibitors are added to a composition to improve its pot life and obtain a stable curable composition. However, to avoid a decrease in curing rate, the curable composition of the present invention shall not contain a hydrosilylation inhibitor. On the other hand, a hydrosilylation inhibitor may be added to a composition to extend its pot life. Hydrosilylation inhibitors are well known in the art, and examples include alkyne alcohols such as 1-ethynylcyclohexane-1-ol, 2-methyl-3-butyne-2-ol, 3,5-dimethyl-1-hexyne-3-ol, and 2-phenyl-3-butyne-2-ol; enyne compounds such as 3-methyl-3-penten-1-yne and 3,5-dimethyl-3-hexen-1-yne; and 1,3,5,7-tetramethyl Examples include methyl alkenylsiloxane oligomers such as 1,3,5,7-tetravinylcyclotetrasiloxane and 1,3,5,7-tetramethyl-1,3,5,7-tetrahexenylcyclotetrasiloxane, alkoxysilanes such as dimethylbis(1,1-dimethyl-2-propinoxy)silane and methylvinylbis(1,1-dimethyl-2-propinoxy)silane, and triaryl isocyanurate compounds.
[0067] In the UV-curable organopolysiloxane composition of the present invention, when a hydrosilylation reaction inhibitor is used, there is no particular amount of the hydrosilylation reaction inhibitor, but preferably the hydrosilylation reaction inhibitor is used in the range of 0.0001 to 1 part by mass, 0.01 to 1 part by mass, or 0.01 to 0.1 parts by mass per 100 parts by mass of the total amount of components (A) to (C).
[0068] [UV-curable organopolysiloxane composition] The UV-curable organopolysiloxane composition of the present invention contains components (A), (B), and (C) as essential components, is substantially free of organic solvents, and has a viscosity of over 80 mPas and up to 500 mPas when measured at 25°C using an E-type viscometer. When the viscosity of the composition is within this range, the composition has excellent coating ability and can efficiently produce a high-quality coating layer.
[0069] The viscosity of the overall composition is preferably in the range of 100 to 500 mPas, more preferably 100 to 350 mPas, and particularly preferably 200 to 350 mPas. In this embodiment, substantially free of organic solvents means that the content of organic solvents is less than 0.05% by mass of the overall composition, preferably below the detection limit when analyzed by an analytical method such as gas chromatography. In the present invention, the desired viscosity of the composition can be achieved by controlling the molecular structure and molecular weight of component (A) and component (B).
[0070] In the curable composition of the present invention, depending on the molecular lengths of components (A) and (B), the number of alkenyl groups or silicon-bonded hydrogen groups per molecule, the bonding positions of these reactive functional groups in the molecule, its molecular structure, the desired physical properties of the cured product therefrom, and its curing rate can be achieved, and the viscosity of the curable composition can be designed to have the desired value. Furthermore, the cured product obtained by curing the curable composition of the present invention is also included in the scope of the present invention.
[0071] The hardness of the cured article of the present invention is preferably 30 or higher, as measured by a Type D durometer at 25°C. A cured article having this hardness can be applied as a cured optical article such as a stamp material that has good release properties for articles having patterns created by nanoimprint lithography, thus contributing to improved productivity in the nanoimprint lithography process. On the other hand, if the hardness of the cured article is too high, its brittleness increases, which may lead to lower productivity and is therefore undesirable. The preferred Type D durometer hardness of the cured article of the present invention is 30 or higher and 70 or lower.
[0072] There are no particular restrictions on the form of the cured body obtained by curing the composition of the present invention. The form of the cured body can be a thin film coating layer, a molded product such as a sheet, or a filler obtained by injecting it into a specific location in an uncured state and curing it. Furthermore, the cured body can be used as a sealing material or intermediate layer applied to laminates or display devices, etc. The cured body obtained from the composition of the present invention is preferably a coating layer having a thin film form, a molded material having a thin film form, and is particularly preferably an insulating molded material having a thin film form.
[0073] The curable composition of the present invention is suitable as an insulating coating agent, potting agent, or molding material having a thin film form for electronic and electrical devices, and is particularly suitable as a stamping material applied to nanoimprint lithography processes.
[0074] [Other additives] Various additives may be added to the composition of the present invention as desired. Examples of additives that can be used include release agents, leveling agents, UV absorbers, antioxidants, and fillers (reinforcing fillers, insulating fillers, thermally conductive fillers, and other functional fillers). Furthermore, thixotropic agents may be added to the composition of the present invention as needed, particularly when used as a potting agent or sealing agent.
[0075] The composition can be prepared by uniformly mixing components (A) to (C) together with other components, as needed. When preparing the composition, the mixture can be mixed at room temperature using various stirrers or kneaders, and may be mixed while adding heat as needed. There are no specific restrictions on the order in which the components are added. They can be mixed together in any order.
[0076] Furthermore, the composition can be a one-component composition, or, considering its storage stability, a multi-component composition such as a two-component composition that is mixed before use. Specifically, in the case of a two-component composition, it is preferable that the first component contains a part of component (A) and a catalyst component (C), and the second component contains a part of component (A) and a crosslinking component (B). Furthermore, other optional components can be added to any of the components, but from the viewpoint of reactivity when all components are mixed, it is preferable to add the hydrosilylation reaction inhibitor to the second component containing component (B).
[0077] This composition can be cured at a relatively low temperature range, including room temperature (e.g., 15-80°C), after irradiation with high-energy rays such as UV rays. Furthermore, the curing reaction of this composition can be controlled to a desired rate by the content of the catalyst metal in component (C), and the type and amount of the hydrosilylation reaction inhibitor.
[0078] [Application] The UV-curable organopolysiloxane composition of the present invention can be cured not only by ultraviolet light but also by electron beams, which is another embodiment of the present invention.
[0079] The curable composition of the present invention has low viscosity and is particularly useful as a material for forming insulating layers for electronic and electrical devices, and as a stamping material applied to nanoimprint lithography processes. The curable composition of the present invention can be applied to a substrate or sandwiched between two substrates, at least one of which contains a material that transmits ultraviolet light or electron beams, and can be cured by irradiation with ultraviolet light or electron beams to form an insulating layer. In this case, the composition of the present invention can be patterned when applied to the substrate, and the composition can then be cured. Alternatively, the composition can be applied to a substrate, leaving cured and uncured portions during curing by irradiation with ultraviolet light or electron beams. The uncured portions can then be removed with a solvent to form an insulating layer with a desired pattern.
[0080] The curable composition of the present invention is suitable as a material for forming insulating layers in touch panels, displays, and other display devices because its cured body has good transparency. In this case, any desired pattern can be formed on the insulating layer, as described above, if necessary. Furthermore, because the cured body has high hardness and release properties, it is suitable as a stamping material applied to nanoimprint lithography processes.
[0081] Furthermore, the curable composition can also be used to form an insulating coating layer (insulating film) by curing it after coating it onto an article. Therefore, the composition of the present invention can be used as an insulating coating agent. Moreover, the cured product formed by curing the curable composition of the present invention can be used as an insulating coating layer. In addition, the cured body obtained by curing the curable composition of the present invention can be used as an insulating coating layer for electronic and electrical devices, an insulating potting agent, and a stamping material applied to nanoimprint lithography processes.
[0082] The present invention will be further described below based on examples, but the present invention is not limited to the following examples. [Examples]
[0083] The UV-curable organopolysiloxane composition and its cured product of the present invention will be described in detail based on examples. Furthermore, the measurements and evaluations in the examples and comparative examples were performed as follows.
[0084] [Viscosity of organopolysiloxanes and curable organopolysiloxane compositions] The viscosity (mPa·s) at 25°C was measured using a rotational viscometer (E-type viscometer VISCONIC EMD, manufactured by TOKIMEC CORPORATION).
[0085] [Preparation of curable organopolysiloxane compositions] The quantities of each material listed in Table 1 below were placed in a brown plastic container and thoroughly mixed using a planetary mixer to prepare a curable organopolysiloxane composition.
[0086] [Preparation of cured products from curable organopolysiloxane compositions] Approximately 0.65 g of a curable organopolysiloxane composition was poured between two glass substrates with a 1 mm thick spacer. LED light with a wavelength of 365 nm was applied at a rate of 4000 mJ / cm² through one of the glass substrates. 2 The composition was irradiated with an energy exposure dose and cured by heating in an 80°C oven for 30 minutes to prepare a plate-shaped organopolysiloxane cured body with sides of 25 mm and a thickness of 1 mm.
[0087] [Appearance of cured products from curable organopolysiloxane compositions] The appearance of the plate-shaped organopolysiloxane cured material obtained by the above method was visually evaluated.
[0088] [Hardness of cured products of curable organopolysiloxane compositions] Four plate-shaped organopolysiloxane cured bodies obtained by the above method were stacked, and the Type D durometer hardness at 25°C was measured using a digital hardness tester (Asker automatic rubber hardness tester, manufactured by KOUBUNSHI-KEIKI CORPORATION).
[0089] [Toughness of cured products of curable organopolysiloxane compositions] After the hardness measurement, the upper layer of the hardened material was visually inspected, and its toughness was evaluated according to the following criteria: No "good" external changes were observed. A slight crack was observed at the contact point of the needle edge of the "NG1" hardness tester. A clear crack was observed in "NG2".
[0090] [Examples and Comparative Examples 1] UV-curable organopolysiloxane compositions with the compositions (parts by mass) shown in Table 1 were prepared using the following components. (A1)(Me3SiO 1 / 2 ) 0.38 (Me2ViSiO 1 / 2 ) 0.08 (SiO 4 / 2 ) 0.54 A branched organopolysiloxane represented by , with a molecular weight of 6,000. (A2a)(Me3SiO 1 / 2 ) 0.48 (Me2ViSiO 1 / 2 ) 0.14 (SiO 4 / 2 ) 0.38 A branched organopolysiloxane represented by , with a molecular weight of 1,200. (A2b)(Me2ViSiO 1 / 2 ) 0.8 (SiO 4 / 2 ) 0.2 A branched organopolysiloxane represented by , with a molecular weight of 432. (A3) Dimethylpolysiloxane, in which both ends of the molecular chain are sealed with dimethylvinylsiloxy groups and has a viscosity of 60 mPas. (B1) MQ-type branched organopolysiloxane having a dimethylhydrogensiloxy group and a hydrogen content of 1.0% by mass. (B2) Polymethylhydrogensiloxane in which both ends of the molecular chain are sealed with trimethylsiloxy groups and the hydrogen content is 1.4% by mass. (C)(cyclopentadienyl)trimethylplatinum(IV) complex
[0091] [Table 1]
[0092] As shown in Table 1, the UV-curable organopolysiloxane compositions of the present invention (Examples 1-6) have a viscosity at 25°C suitable for application to substrates as coating agents by spin coating or other coating procedures, and possess high transparency. The cured products obtained by UV irradiation and subsequent heating are transparent and have sufficiently high hardness. Therefore, the UV-curable organopolysiloxane compositions and their cured products of the present invention are suitable as stamp materials applied to nanoimprint lithography processes. On the other hand, compositions with too low a viscosity (Comparative Examples 2 and 3) failed to provide cured products with sufficient toughness. Furthermore, the hardness of the cured product from the composition lacking component (A2) (Comparative Example 4) was insufficient. Also, if the alkenyl content of the composition (Comparative Example 1) is outside a specific range, the viscosity is too high and it is not suitable as a coating agent.
[0093] Industrial applicability The UV-curable organopolysiloxane composition of the present invention is particularly suitable for the applications described above, and is especially suitable as a material for forming stamp materials applied to nanoimprint lithography processes.
Claims
1. A UV-curable organopolysiloxane composition, (A) The following components (A1), (A2), and (A3): (A1) A branched organopolysiloxane having two or more alkenyl groups in the molecule and a molecular weight of 2,500 or more. (A2) Branched organopolysiloxanes having two or more alkenyl groups in the molecule and a molecular weight of less than 2,500, and (A3) A linear organopolysiloxane having two or more alkenyl groups in the molecule, A mixture of alkenyl-functional organopolysiloxanes, (B) An organopolysiloxane having two or more silicon-bonded hydrogen atoms in the molecule in an amount such that the molar ratio of the silicon-bonded hydrogen atoms in component (B) to the alkenyl groups in component (A) is in the range of 0.5 to 4.0, (C) photoactivatable hydrosilylation catalyst, The mass ratio of components (A1), (A2), and (A3) satisfies the following equation (1): [(A1)+(A2)] / (A3)≧1.5 (1) The amount of alkenyl groups X (in mmol) per 100 g of the entire composition satisfies the following formula (2): 110 ≤ X ≤ 220 (2) The viscosity of the entire composition, measured at 25°C using an E-type viscometer, is in the range of over 80 mPas to 500 mPas or less. A UV-curable organopolysiloxane composition that is substantially free of organic solvents.
2. If the total mass of components (A) to (C) in the composition is 100 parts by mass, then the parts by mass of components (A1), (A2), and (A3) are as follows: (A1): 25 to 75 parts by mass, (A2): 3 to 60 parts by mass, and (A3): 5 to 40 parts by mass A UV-curable organopolysiloxane composition according to claim 1, satisfying the conditions.
3. The UV-curable organopolysiloxane composition according to claim 1, wherein component (A3) is a linear organopolysiloxane having an alkenyl group at its molecular terminus.
4. The UV-curable organopolysiloxane composition according to claim 1, wherein component (B) is a linear organopolysiloxane having two or more silicon-bonded hydrogen atoms in the molecule.
5. Component (A1) has an alkenyl group and the following average unit formula: (R 1 3 SiO 1/2 ) a1 (R 1 2 SiO 2/2 ) b1 (R 1 SiO 3/2 ) c1 (SiO 4/2 ) d1 (3) (In the formula, R 1 These are, independently, monovalent hydrocarbon groups having 1 to 12 carbon atoms. All R 1 The UV-curable organopolysiloxane composition according to claim 1, wherein at least two of the members are alkenyl groups having 2 to 12 carbon atoms, and a1, b1, c1, and d1 are represented by the following conditions: a1 + b1 + c1 + d1 = 1, 0 ≤ a1 ≤ 0.5, 0 ≤ b1 ≤ 0.4, 0 ≤ c1 ≤ 0.8, and 0 ≤ d1 ≤ 0.7, 0.5 ≤ c1 + d1 ≤ 0.
8.
6. Component (A2) has an alkenyl group and the following average unit formula: (R 2 3 SiO 1/2 ) a2 (R 2 2 SiO 2/2 ) b2 (R 2 SiO 3/2 ) c2 (SiO 4/2 ) d2 (4) (In the formula, R 2 These are, independently, monovalent hydrocarbon groups having 1 to 12 carbon atoms. All R 2 The UV-curable organopolysiloxane composition according to claim 1, wherein at least two of the groups are alkenyl groups having 2 to 12 carbon atoms, and a2, b2, c2, and d2 are represented by the following conditions: a2 + b2 + c2 + d2 = 1, 0 ≤ a2 ≤ 0.5, 0 ≤ b2 ≤ 0.8, 0 ≤ c2 < 0.5, and 0 ≤ d2 < 0.5, 0 < c2 + d2 < 0.5).
7. The UV-curable organopolysiloxane composition according to claim 1, wherein the hardness of the cured body obtained by curing the composition is 30 or more and 70 or less, as measured at 25°C using a Type D durometer.
8. The UV-curable organopolysiloxane composition according to claim 1, wherein the viscosity of the entire composition, as measured at 25°C using an E-type viscometer, is in the range of 100 to 350 mPas.
9. The UV-curable organopolysiloxane composition according to claim 1, wherein component (C) is an unsubstituted or alkyl-substituted (cyclopentadienyl) trialkyl platinum complex.
10. An insulating coating agent comprising the UV-curable organopolysiloxane composition described in any one of claims 1 to 9.
11. A cured body obtained by curing a UV-curable organopolysiloxane composition according to any one of claims 1 to 9.
12. Use of the UV-curable organopolysiloxane composition according to any one of claims 1 to 9 as a stamp-forming material applied to nanoimprint lithography.
Citation Information
Patent Citations
silicone skin adhesive gel
JP2007532179A
Curable organopolysiloxane composition and optical semiconductor device
JP2020530502A
Silicone gel composition
US20170022326A1
Sealant for optical semiconductors and optical semiconductor device
WO2011125463A1
Curable silicone composition for die bonding use
WO2019003995A1